0212 Habitual Heavy Alcohol Drinking in Healthy Adults is Associated With Reduced Circadian Photoreceptor Responsivity to Light. (25th May 2022) - Burgess, Helen; Rizvydeen, Muneer; Kikyo, Fumitaka; Kebbeh, Nema; Tan, Michael; Roecklein, Kathryn; Hasler, Brant; King, Andrea; Cao, Dingcai
Abstract: Introduction: Habitual alcohol consumption and circadian timing are interconnected. Numerous studies have reported that heavy alcohol use is associated with eveningness. Only two studies have assessed the dim light melatonin onset (DLMO) in the context of habitual alcohol use, and both reported a shorter DLMO-midsleep interval was associated with heavier alcohol consumption. A gap in this research is the potential impact of alcohol use on the primary circadian photoreceptor, the intrinsically photosensitive retinal ganglion cells (ipRGCs), which influence circadian timing. This study aimed to compare sleep, circadian timing, and photoreceptor responsivity between light and heavy alcohol drinkers. Methods: Participants were healthy (average age 27 years) and included 28 light (average 2.6 drinks/week) and 50 heavy (average 17.9 drinks/week) drinkers. They participated in an 8-day study protocol: 1 week of adlib sleep monitored with wrist actigraphy, followed by a 9-hour laboratory session with a photoreceptor responsivity (post-illumination pupil response, PIPR) and circadian phase assessment. Participants passed a breathalyzer test at the start of the laboratory session. Results: Both drinking groups were good sleepers with minimal mood disturbance. Consistent with earlier studies, the heavy drinkers had more eveningness (p=0.029), and a trend for a shorter DLMO-midsleep interval (p=0.059) as compared to the light drinkers. The PIPR in the heavy drinkers was significantly smaller than in the light drinkers (p=0.006), suggesting reduced circadian photoreceptor responsivity in the heavy drinkers. In the light drinkers, a larger PIPR in the evening, reflecting greater sensitivity to phase-delaying light, was significantly associated with a later DLMO (r=0.42, p=0.028). However, this relationship was absent in the heavy drinkers (r=-0.07, p=0.68). Conclusion: The findings replicate previous work examining the relationship between chronotype, DLMO, and habitual alcohol consumption. For the first time, circadian photoreceptor responsivity was examined, and found to be significantly reduced in heavy alcohol drinkers as compared to light alcohol drinkers. This finding is consistent with prior rodent studies that found reduced phase shifts to light with acute or chronic alcohol consumption, and suggests that habitual heavy alcohol use may impair the circadian response to light in humans. Support (If Any): Grant awarded from NIAAA R01 AA023839.